ESTADO DA ARTE DE MODELOS MATEMÁTICOS QUE PREDIZEM O TEMPO DE VIDA DE BATERIAS - Duarte, Kelly P.; Machado, Marlon V.; Kuhn, Igor; Sausen, Airam T. Z. R.; Sausen, Paulo S. (Salão do Conhecimento, 2013)
Resumo